2018
DOI: 10.1155/2018/3172679
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hyperbaric Oxygen Therapy on Functional Impairments Caused by Ischemic Stroke

Abstract: Background While research suggests a benefit of hyperbaric oxygen therapy (HBOT) for neurologic injury, controlled clinical trials have not been able to clearly define the benefits. Objective To investigate the effects of HBOT on physical and cognitive impairments resulting from an ischemic stroke. Methods Using a within-subject design a baseline for current functional abilities was established over a 3-month period for all subjects (n=7). Each subject then received two 4-week periods of HBOT for a total of 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…Some papers [ 24 , 27 , 28 ] reported that HBOT is able to stimulate neuroplasticity even years after a brain insult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some papers [ 24 , 27 , 28 ] reported that HBOT is able to stimulate neuroplasticity even years after a brain insult.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms underlying HBOT brain effects have to be clearly defined yet [ 28 ], it seems that many factors are involved: inflammation modulation [ 25 ], strengthening of the antioxidant endogenous system [ 29 , 30 ], neoangiogenesis stimulation in the damaged tissues [ 21 , 31 ] and tissue repair stimulation by bone marrow staminal cells mobilization [ 32 ]. All these mechanisms could account for HBOT ability to stimulate neoangiogenesis and neuroplasticity even years after the brain insult.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that aside from the decrement in the secretion of proinflammatory cytokines, HBOT attenuates neuroinflammation via enhancement of immune cell secretion of anti-inflammatory cytokines [28,88,89]. In animal models, HBOT increased the expression levels of mRNA encoding the anti-inflammatory cytokine interleukin (IL-4), as measured by real-time quantitative PCR [28], and increased the concentration of the anti-inflammatory cytokine IL-10 in the cortices, as measured by ELISA [88].…”
Section: The Impact Of Hbot On Neuroinflammationmentioning
confidence: 99%
“…In animal models, HBOT increased the expression levels of mRNA encoding the anti-inflammatory cytokine interleukin (IL-4), as measured by real-time quantitative PCR [28], and increased the concentration of the anti-inflammatory cytokine IL-10 in the cortices, as measured by ELISA [88]. Changes in anti-inflammatory cytokines were found in human patients with various neurological conditions as well [89].…”
Section: The Impact Of Hbot On Neuroinflammationmentioning
confidence: 99%
“…The effectiveness of HBO is related to improving hypoxia, microcirculation, and metabolism and preventing further progression of deleterious secondary effects [12]. A large number of animal experiments and clinical trials have shown that HBO alleviates infarct size and oedema and reduces the permeability of the blood-brain barrier, which has a positive effect on ischemic stroke [13][14][15][16]. Spatial memory has been effectively improved in rats with ischemic hypoxic brain injury, and this improvement may be attributable to the preservation of damaged cortical and hippocampal cells [17].…”
Section: Introductionmentioning
confidence: 99%